Design and development an ergonomic SMED’s external prerparation for small press die at FKP lab - Che Engku Nuzuwal Ikram, Che Engku Abdullah (2013)
Single Minute Exchange of Dies (SMED) mainly focuses on recognition of internal and external activities. It is concerned particularly with transferring internal activities into external ones in as many numbers as possible, by also minimizing the internal ones. The major problem when operating a press machine is when the process of changing a die to a new one in order to produce other products. The die changing process is too long to be completed. Much energy is used through the process of changing of die includes human and machine. The objective of this project is to design and fabricate good external preparation equipment (prototype) for small press dies as a reflection to the next semester students who will continue this project in order to produce the actual product. The major step through this project is to study current condition of press machine. After study the current condition, went to PHN Industry Sdn Bhd for a pilot visit to get the related information of the project. Then the design idea is come out through the visit after seeing the condition at stamping department at PHN Industry Sdn Bnd. Two conceptual designs are produced using CAD Software which is Catia V5 and the design that fits the condition at Fakulti Kejuruteraan Pembuatan (FKP) laboratory was selected and validated by the supervisor. The selected design stimulated into rapid prototyping machine and fabricated. A prototype of external preparation equipment for small press dies (Die T-Table) is produced using rapid prototyping machine. This project will bring the idea for the next semester final year student who will continue this project and will assist them in order to produce the actual Die T-Table to be attached at stamping machine in FKP Laboratory.